Recommendations for screening of donor and recipient prior to solid organ transplantation and to minimize transmission of donor–derived infections. (September 2014) - Len, O.; Garzoni, C.; Lumbreras, C.; Molina, I.; Meije, Y.; Pahissa, A.; Grossi, P.; ,
Abstract: In the context of solid organ transplantation, screening of recipients and organ donors is crucial, and should be performed with great rigour to minimize the reactivation or the risk of transmission of certain infectious processes. This review aims to update understanding of the possible pathologies involved, as well as of emerging infections that, as a result of globalization, are gaining increasing prominence on a daily basis.